An Examination of Cultural-Economic Model and Public Relations in The Malaysian Islamic Banking System - Thaker, Mohamed Asmy Mohd Thas; Thaker, Hassanudin Mohd Thas (Journal of Islamic Finance, 2015)
By adopting the study by Gaither and Kandari on cultural-economic model of, the current study was designed to analyse the cultural-economic model of public relations practice of two prominent Islamic banks (full-fledged Islamic bank and Islamic window bank) in Malaysia. This study is mainly focusing on their communication tool particularly websites and relevant reports. The study is advancing the understanding of Islam and public relations in the context of Islamic banking institution in Malaysia, an understudied area in public relation literature and enlightens the relationship between religion and public relations. The analysis has identified six Islamic value orientations elements especially respect for religious authority, affinity with the past, fatalism, communal kinship, attachment to the eternal life and spirituality and idealism relative to public relation practice among the particular Islamic banks. The study concludes with observation that there is inseparable relationship between religion and culture in the context of Islamic banking industry in Malaysia.